Elite basketball players spend 75% of playing time with a heart rate greater than 85% of its maximum value - McInnes, S. E.; Carlson, J. S.; Jones, C. J.; McKenna, M. J.
The relative amount of time spent at different intensity levels in elite basketball was studied. Results: Of all strides/sprints, 51% lasted longer than 1.5 s, 27% longer than 2 s, 12% longer than 3 s and 5% longer than 4 s. On average, about 10% of total time and 15% of live time was spent engaged in high intensity activity (see figure 1). There were no differences in the movement patterns between the quarters of play. High intensity run efforts occurred once every 21 s of live time on average, and the average duration was 1.7 s. It is clear that only a small percentage of live time in basketball is spent in high intensity activity. The majority of time is spent engaged in more aerobic activities. In addition, as only 35% of the time spent in stand/walk was during live time, the results suggest that the format of the game plays an important role in reducing the overall movement demands of competition. As 31% of live time was spent in shuffling movements, of which 20% was spent in high-intensity shuffling movements, it appears that shuffling requires a considerable portion of the total energy demands of basketball and, therefore, may be an important aspect of preparing athletes for competition. The mean heart rate during total time was 165 beats per minute. Figure 2 shows that approximately 65% of total time (and 75% of live time) was spent with a heart rate greater than 85% of its maximum (as measured during a treadmill running test to voluntary fatigue). The apparent inconsistency between the percentages of time spent in high intensity activity and with a high heart rate suggests that upper body activities such as shooting, rebounding and maintaining position against an opponent - none of which were measured in this study - are likely to contribute to the physical demands of basketball.